2016
DOI: 10.1080/08998280.2016.11929397
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Autonomic Neuropathy

Abstract: Cardiovascular autonomic neuropathy often goes unrecognized. We present a case of a 22-year-old man with multiple manifestations of this disease, including weakness, dizziness, fatigue, tachycardia, abnormal QTc, and orthostasis, which occurred 2 years after his type 1 diabetes diagnosis. He exhibited parasympathetic denervation with resting tachycardia and exercise intolerance but also had evidence of orthostatic hypotension, which suggests sympathetic denervation. He did not have complete cardiovascular auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This therapeutic scheme common in the treatment of CKD appears to be an evident pathophysiological mechanism leading to OH since diuretics and dehydration activate the RAA system, thus augmenting the effects of ACE-I and β-blockers. This is confirmed by findings from other studies [4,5,6]. It should be stressed that polypharmacy and drug interactions are the most frequent risk factors for the development of OH [36].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This therapeutic scheme common in the treatment of CKD appears to be an evident pathophysiological mechanism leading to OH since diuretics and dehydration activate the RAA system, thus augmenting the effects of ACE-I and β-blockers. This is confirmed by findings from other studies [4,5,6]. It should be stressed that polypharmacy and drug interactions are the most frequent risk factors for the development of OH [36].…”
Section: Discussionsupporting
confidence: 85%
“…Its clinical manifestation has a wide spectrum, ranging from very mild symptoms, i.e., weakness, dizziness and fainting, to serious conditions accompanied by loss of consciousness. Within the spectrum of civilization diseases, OH coexists with arterial hypertension (AH), metabolic disorders like diabetes, chronic kidney disease (CKD), dialysis therapy, or toxemia with secondary damage to the ANS (long-term alcohol-dependence, long-term drug use, drug induced damage), and electrolyte imbalance [5,6,7]. A model disease that illustrates this problem is diabetes, and the coexistence of OH and AN in diabetic patients has been quite thoroughly researched [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no universal standard method for detecting CAN, and it is suggested that more than one test should be conducted to enhance the sensitivity and reliability of CAN diagnosis [ 19 ]. In this setting, several tests with different degrees of accuracy, such as CARTs, HRV, and nuclear imaging, are available[ 61 , 69 , 81 , 82 ].…”
Section: Critical Reflectionmentioning
confidence: 99%
“…These disorders that develop in the autonomic system are explained by the neurotropic effects of the leprosy bacilli that infiltrate the sympathetic and parasympathetic fibers. The autonomic and intrinsic cardiac involvement affects ventricular repolarization and prolongs QTc and Tp-e intervals (14,15). It is now well known that QT and QTc prolongation causes life-threatening arrhythmias, and it has also started to be realized that LAH is important regarding cardiac comorbidities.…”
Section: Discussionmentioning
confidence: 99%